Re-Encountering traditional Indigenous activities through a psychosocial intervention in Sunrise community - Calegare, Marcelo Gustavo Aguilar; Ferreira, Mayara dos Santos; Sampaio, Cláudia Regina Brandão; Clennon, Ornette D. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
This article makes a reading and reflection of a psychosocial intervention taken at Sunrise Community (SRC), a multi-ethnic indigenous settlement (12 indigenous groups and non-indigenous) located in Manaus, Amazonas, Brazil. Through Community Social Psychology approach and Participatory Action Research, weekly visits were made for five months. Interviews, meetings, and informal conversations with leaders and residents were recorded in field diaries. Among the concerns residents had were: communication difficulties and the distancing of traditional practices that are associated with identity issues and historical inter-ethnic conflicts that mark relations in the SRC. As a result, the community held a Meeting of Ethnic Groups to gather members of SRC and other indigenous settlements for a day of celebration, to re-encounter traditional customs and practices. We acted as facilitator, favoring reflections on the roles, struggles and autonomy in the SRC and suggesting a horizontal model in the interactions. The organization and preparation of the celebration increased the interaction among the residents, although the different forms of participation and the ambiguity of identity markers. Reflections on postcolonialism and power relations have made it possible to weave important considerations into the findings, especially to reflect on the political dimension in claiming the rights of these groups.